Calibration of FHCal with cosmic muons at the BM@N experiment. (December 2020) - Izvestnyy, A; Karpushkin, N; Guber, F; Morozov, S; Petukhov, O
Abstract: The forward hadron calorimeter (FHCal) is one of the sub-detectors of the BM@N experimental setup at JINR, Dubna. It consists of 54 lead-scintillator "sandwich" type modules of two types with the transverse sizes 20 × 20 cm 2 and 15 × 15 cm 2 . These two types of modules are subdivided into 10 and 7 individual longitudinal sections, respectively. Each section provides the independent light and amplitude signal readout with one silicon photomultiplier (MPPC). High signal to noise ratio of MPPC allows to detect cosmic rays with low energy depositions in FHCal longitudinal sections. A method for cosmic muon track reconstruction is discussed. A procedure for energy calibration based on muon track length and energy deposition in each section is proposed. Experimental results of FHCal cosmic calibration are presented.